PENGARUH STRUKTUR UTANG TERHADAP PROFITABILITAS: STUDI EMPIRIS PADA PERUSAHAAN NON-KEUANGAN DI INDONESIA - Nurul Tyas Andini; Liza Handoko (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The purpose of this study is to examine the effect of capital structure on corporate financial performance, as measured by profitability. Capital structure is assessed using Short-term Debt (STD) and Long-term Debt (LTD), while profitability is evaluated through Return on Assets (ROA) and Net Profit Margin (NPM). The research data comprises 807 non-financial companies registered on the Indonesia Stock Exchange. Panel data regression is employed for the analysis over the observation period from 2015 to 2024, estimated using the Fixed Effects Model. The panel regression results indicate that both STD and LTD significantly and negatively impact profitability, as measured by ROA and NPM. Overall, the findings suggest that capital structure is a critical factor that should be considered in relation to the company’s profitability.